2005
DOI: 10.1111/j.1600-0404.2005.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension in Dubai: nature and prognosis

Abstract: Idiopathic intracranial hypertension has relatively benign course in this part of the world and more aggressive treatment is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…21 and Sadaah et al reported on 50 IIH patients from Dubai (UAE) and again obesity was the most commonly associated risk factor. 10 Two studies conducted in Israel published in 2001 and 2014 by the same authors showed an increased percentage of obesity of 57.2% and 83.4%, respectively, as a major risk factor for IIH. 19,20 The pathophysiological mechanism of obesity in IIH remains unclear.…”
Section: Role Of Obesity On Iihmentioning
confidence: 97%
See 1 more Smart Citation
“…21 and Sadaah et al reported on 50 IIH patients from Dubai (UAE) and again obesity was the most commonly associated risk factor. 10 Two studies conducted in Israel published in 2001 and 2014 by the same authors showed an increased percentage of obesity of 57.2% and 83.4%, respectively, as a major risk factor for IIH. 19,20 The pathophysiological mechanism of obesity in IIH remains unclear.…”
Section: Role Of Obesity On Iihmentioning
confidence: 97%
“…6 In contrast, obesity is not as significant of a risk factor in men as it has been reported by available published studies in GCC but the study numbers are limited. 10,14 …”
Section: Role Of Obesity On Iihmentioning
confidence: 98%
“…Emerging evidence is showing that an increased TLPD is important in the pathogenesis of glaucoma [2][3][4][5][6], whereas papilledema and anterior disk movement occurs with a reduction or reversal of the TLPD [8,9]. Traditionally, glaucoma pathogenesis has been ascribed to elevated IOP with little regard for CSFp, while diseases of elevated CSFp like IIH have paid little attention to IOP.…”
Section: The Hypothesismentioning
confidence: 99%
“…Ophthalmoscopy of the optic nerve head shows a swollen optic nerve that bulges forward with edema present in the surrounding retinal nerve fiber layer. This disk swelling occurs when CSF pressure rises to between 17 and 45 mmHg [8,9] and is due to a loss of CSF outflow conductance. Fifty percent of patients will completely resolve within 3-6 months of CSF lowering treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Prognosis is variable, with severe visual loss occurring in up to 10% of cases.8 Although few series have specifically evaluated racial differences in IIH, it has been suggested that black patients may have more severe outcomes from IIH.9 -11 The purpose of this study was to compare the characteristics of IIH in blacks and nonblacks.…”
Section: Introductionmentioning
confidence: 99%